A Teacher Identity and Role Model Characteristics of Kru Chawengsak Phothisombat - Suwanphithak, Weerakit; Laovanich, Vitchatalum; Chuppunnarat, Yootthana (Journal of Fine and Applied Arts Khon Kaen University, 2022)
This qualitative research study aims to examine a teacher identity and role model characteristics of Kru Chawengsak Phothisombat. The methodology process began with specifying sources and key informants which includes 1) documents and related research and 2) key informants that were drawn using purposive sampling and snowball sampling. The research tools of this study were document and electronic media form, Semi-structural interview questions, and observation form. The data collected by participant observation, and Informal interview. In the data analysis process, content analysis was employed, and triangulation was used for data validation. The findings have shown that the teacher identity and role model characteristics of Kru Chawengsak Phothisombat was divided into 4 parts: 1) To be proficient in Thai music in both theoretical and performance advance skills and being widely well-known by Thai musicians, 2) Having teaching abilities, to begin with analyzing student background ability, having good pedagogy, and using the authentic assessment, 3) Full of mercy to all students, not only giving full of knowledge transparently, but also always take good care of the students as members of the family, and 4) Being a positive role model for students, in terms of good personality, ability and skillfulness, adaptability, and gratitude.